Analisis Faktor-Faktor Penyebab Kurangnya Literasi Membaca Buku di Sd Yayasan Duta Harapan Bukit Sion Medan - Ristama Nainggolan; Ratna Dewi Nababan; Santi Lorensa Junita Sianturi; Nur Habibah; Ivan Fauza Ishadi; Lasenna Siallagan (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Factors causing low reading knowledge among students at SD Yayasan Duta Harapan Bukit Sion Medan include the social, economic and educational conditions of the school environment. Factors such as limited access to various reading materials, lack of family support for reading habits, and uninteresting learning methods may be the main causes. In addition, students' intrinsic factors such as lack of interest in reading and undeveloped reading skills also need to be considered. This research is important in identifying the problems and developing appropriate strategies to improve reading skills in the school. This study aims to analyze the factors that cause low reading knowledge at SD Yayasan Duta Harapan Bukit Sion. This method uses a qualitative approach, where data is collected through interviews with teachers and students. The results showed that some of the factors causing students' low reading skills are laziness, physical or psychological disorders, lack of interest and the use of technology. Teachers play an important role in preparing interesting lesson plans, providing special support and using technology. Literacy in schools helps improve students' interest and reading skills through habituation, development and gradual learning. The implications of the findings highlight the need for collaborative efforts between schools and parents to improve reading skills in schools.